Hubungan Etika Lingkungan Dan Kesadaran Lingkungan Masyarakat Desa Sukamaju Kecamatan Air Nipis Kabupaten Bengkulu Selatan - Ranti Uchera; Reflis Reflis; Satria Putra Utama; Yenita Ekasari; Dwi Maryani; Essy Anesta Asdami (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Indonesia is one of the countries that is the lungs of the world. This country has extraordinary environmental potential, starting from natural resource conditions (biological and non-biological diversity), geographical conditions, and demographic conditions that other countries do not have. The gifts given by Allah SWT to all His creatures, especially humans, must be used well or wisely. Utilizing these gifts to meet the needs of living creatures must be accompanied by great responsibility in protecting and managing them so that their sustainability is maintained (sustainability). Ironically, if we look at the current facts, the situation is the opposite. Our various daily activities, from small to large scale, individually and collectively (society), contribute to air pollution, water pollution, soil pollution, land degradation, loss of biodiversity and germplasm, resource and energy crises, and the peak is global warming. The behavior of throwing rubbish and waste carelessly, wasting energy, using vehicles with high emissions, and various other bad activities among the majority of Indonesian people is still very worrying. This is still done by many people who are highly educated or not, rich or poor, young and old, and men and women.